2011
DOI: 10.1104/pp.111.177196
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxins and NADPH-Dependent Thioredoxin Systems in the Model Legume Lotus japonicus      

Abstract: Peroxiredoxins (Prxs), thioredoxins (Trxs), and NADPH-thioredoxin reductases (NTRs) constitute central elements of the thioldisulfide redox regulatory network of plant cells. This study provides a comprehensive survey of this network in the model legume Lotus japonicus. The aims were to identify and characterize these gene families and to assess whether the NTR-Trx systems are operative in nodules. Quantitative reverse transcription-polymerase chain reaction and immunological and proteomic approaches were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 72 publications
1
46
0
Order By: Relevance
“…Among the target proteins of TRX m, 2-Cys peroxiredoxin is an important antioxidant for hydrogen peroxide (H 2 O 2 ) detoxification in chloroplast (König et al, 2002;Dietz and Pfannschmidt, 2011;Tovar-Méndez et al, 2011). Previous studies suggest that TRX m proteins are able to reduce the oxidative state of 2-Cys peroxiredoxin to maintain the metabolic balance of reactive oxygen species (ROS; Collin et al, 2003;Chi et al, 2008).…”
Section: Vigs-trx M Plants Accumulate More Reactive Oxygen Species Thmentioning
confidence: 99%
“…Among the target proteins of TRX m, 2-Cys peroxiredoxin is an important antioxidant for hydrogen peroxide (H 2 O 2 ) detoxification in chloroplast (König et al, 2002;Dietz and Pfannschmidt, 2011;Tovar-Méndez et al, 2011). Previous studies suggest that TRX m proteins are able to reduce the oxidative state of 2-Cys peroxiredoxin to maintain the metabolic balance of reactive oxygen species (ROS; Collin et al, 2003;Chi et al, 2008).…”
Section: Vigs-trx M Plants Accumulate More Reactive Oxygen Species Thmentioning
confidence: 99%
“…In general, the main redox-regulatory network in chloroplasts consists of NADPH-dependent TRX reductase C (NTRC), all plastidal TRXs, plastidal peroxiredoxins, and the glutathione/glutaredoxin system (Kirchsteiger et al, 2009;Pulido et al, 2010;Dietz and Pfannschmidt, 2011;Tovar-Méndez et al, 2011). Recently, the comprehensive analysis of an Arabidopsis knockout mutant for NTRC revealed that NTRC may redox regulate several enzymes and thus modulate the expression of genes involved in chlorophyll synthesis (Stenbaek et al, 2008;Lepistö et al, 2009).…”
Section: Redox State Of the Chli Protein In The Leaves Of Vigs Plantsmentioning
confidence: 99%
“…Among the target proteins for these TRX isoforms is 2-Cys Prx, which is involved in peroxide detoxification in the chloroplast during the dark phase (König et al, 2002;Pulido et al, 2010;Dietz, 2011;Tovar-Méndez et al, 2011). TRX-F and TRX-M are able to reduce oxidized 2-Cys Prx (Chi et al, 2008).…”
Section: Accumulation Of Ros In Vigs-trx-f/trx-m Plantsmentioning
confidence: 99%
“…The thiol/disulfide turnover participates in turning on/off the function of proteins and in modifying the activity of transcription factors and enzymes [21]. As the Trxs system is linked to photosynthetic light reactions, its role will be addressed in the next section.…”
Section: Reactive Oxygen Species and Redox Homeostasismentioning
confidence: 99%